Empowering MSMEs in Makmur Village: Assistance in Making Business Identification Numbers (NIB) to Improve the Community's Economy - Nurwahyudi Mampi; Bakri Hasanuddin; Ni Luh Putu Evvy Rossanty; Muh. Riswandi Palawa (PT. Global World Scientific, 2024)
This study aims to analyze the impact of empowerment and assistance in making a Business Identification Number (NIB) for Micro, Small, and Medium Enterprises (MSMEs) in Makmur Village, Palolo District, Sigi Regency. This program was implemented in collaboration between Tadulako University, the Sigi Regency Cooperative and MSME Service, and the Makmur Village Government to provide an understanding to MSMEs regarding the importance of business legality. In this process, many MSMEs, especially the elderly, had difficulty understanding the digital system used for NIB registration. However, with assistance, MSMEs managed to understand and obtain NIBs that provide legal protection and access to various government facilities. The results of the study showed that the mentoring program succeeded in increasing the understanding of MSME actors about the benefits of having a NIB and the importance of business legality. In addition, this empowerment also includes training in financial management, digital marketing, and business development. MSME actors involved in this program become more confident in running their businesses legally and in an organized manner. This program has the potential to strengthen the economy of Makmur Village and the surrounding area by increasing the competitiveness of MSMEs in the global market.